Peran Kebijakan Pemerintah dalam Memperkuat Aliansi Strategis dan Meningkatkan Daya Saing Ekonomi Kreatif - Umu Khouroh; Irany Windhyastiti; Krisnawuri Handayani; Irany Windhyastiti (University of Merdeka Malang, 2019)
This study aims :1) to examine the effect of strategic alliances and government policies on the achievement of competitive advantage of micro, small and medium creative enterprises, 2) to assess the role of government policies in moderating the relationship between strategic alliances and competitive advantage. This study was conducted in 130 micro, small and medium craft enterprises in Malang Raya. Using SEM-PLS in WarpPLS 6.0, this study finds that strategic alliances have significant effects on competitive advantage. Government policy does not moderates the relationship between strategic alliances and competitive advantage, but at the same time it serves as the driver of strategic alliances and the predictor of competitive advantage. Government policies have the highest loading factor, followed by strategic alliances. Thus, micro, small and medium enterprises in creative economy must focus on optimizing strategic alliances to greatly improve their competitive advantage. In addition, the government can driven strategic alliances while providing facilitation, support, and policies that encourage improvements in competitive advantage.https://doi.org/10.26905/jmdk.v7i2.3830